2012
DOI: 10.1177/1087054712457991
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of ADHD and Comorbid Disorders in Iranian Adult Male Prison Inmates

Abstract: ADHD is prevalent in offenders and it is associated with comorbid disorders. The results emphasize the necessity of treatment programs for offenders with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 43 publications
5
30
4
Order By: Relevance
“…Th e hypothesis was not supported. Rather, and contrary to other fi ndings (e.g., Willcutt 2012; Wingo and Ghaemi 2007;Tamam et al 2008;Amiri et al 2010;Hooman and Ganji 2012), prevalence rates were signifi cantly higher on the basis of both selfreports and experts ' ratings and, surprisingly, prevalence was as high as that reported for male Iranian prisoners (Hamzeloo et al 2012). Th e current data do not allow any detailed interpretation of the high prevalence rates found, though it is conceivable that use of DSM-IV criteria rather than ICD-10 criteria might have led to higher prevalence rates.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Th e hypothesis was not supported. Rather, and contrary to other fi ndings (e.g., Willcutt 2012; Wingo and Ghaemi 2007;Tamam et al 2008;Amiri et al 2010;Hooman and Ganji 2012), prevalence rates were signifi cantly higher on the basis of both selfreports and experts ' ratings and, surprisingly, prevalence was as high as that reported for male Iranian prisoners (Hamzeloo et al 2012). Th e current data do not allow any detailed interpretation of the high prevalence rates found, though it is conceivable that use of DSM-IV criteria rather than ICD-10 criteria might have led to higher prevalence rates.…”
Section: Discussioncontrasting
confidence: 78%
“…Compared with data from Willcutt (2012; 6.7% prevalence rate), the prevalence rate of the current sample was signifi cantly higher ( χ 2 ( N ϭ 487, df ϭ 1) ϭ 6.64, p ϭ 0.014). Compared with data from male Iranian prisoners (Hamzeloo et al 2012), the prevalence rate of adult ADHD in this sample did not diff er signifi cantly ( χ 2 ( N ϭ 1682, df ϭ 1) ϭ 0.026, p ϭ 0.935).…”
Section: Prevalence Ratescontrasting
confidence: 75%
See 1 more Smart Citation
“…Considering the behavioural problems and consequences among adults with ADHD and the disorder's comorbidity with other problems (e.g., antisocial personality disorder and drug‐related disorders), it is reasonable to expect that ADHD among adult prisoners is more common than the normal population. Evidences shows that 10–70% of prisoners in different countries suffer from the disorder (Ghanizadeh, Mohammadi, Akhondzadeh, & Sanaei‐Zadeh, ; Gudjonsson, Sigurdsson, Young, Newton, & Peersen, ; Hamzeloo, Mashhadi, & Fadardi, ). The result of a recent meta‐analysis estimating the prevalence of ADHD in incarcerated populations was 25.5% with no significant differences for gender and age (Young, Moss, Sedgwick, Fridman, & Hodgkins, ).…”
mentioning
confidence: 99%
“…The result of a recent meta‐analysis estimating the prevalence of ADHD in incarcerated populations was 25.5% with no significant differences for gender and age (Young, Moss, Sedgwick, Fridman, & Hodgkins, ). Inmates with ADHD were at greater risk of suffering from behavioural problems and psychiatric comorbidities (e.g., substance use disorders, conduct disorder, mood disorders, anxiety disorders, and personality disorders) compared with inmates without ADHD (Hamzeloo et al, ; Young, Adamou, et al, ; Young, Wells, & Gudjonsson, ). The result of a recent meta‐analysis showed that the risk of all psychiatric comorbidity has increased among adult inmate with ADHD.…”
mentioning
confidence: 99%